Wear resistance research of the weld deposit materials under gas abrasive wear - Кудрін, А.П. (Problems of Tribology, 2016)
The method and installation for research of the gas abrasive wear of the materials using the centrifugal method of acceleration of abrasive particles is described. Dependence of structural steels wear and number of materials of weld deposit on the size and speed of the abrasive particles has been obtained. The processes developing on the working surfaces of materials under the action of abrasive particles and processes which lead to a change in the intensity of destruction of surfaces with size increasing and speed of the abrasive particles has been analyzed.